Spatio-temporal variability in the feeding strategy of Andean rodents: the role of ambient temperature and food availability - Ruperto, Emmanuel Fabián; Menéndez, Josefina; Taraborelli, Paula Andrea; Dacar, María Ana; Sassi, Paola Lorena (Springer, 2023)
Animals' diets reflect the morpho-physiological and behavioral responses used to obtain nutrients and energy. While optimal foraging theory predicts them in terms of food availability, the obligatory heat model (OHM) predicts them based on ambient temperature, which affects the activity and/or size of the digestive organs, influencing food digestibility. In the highlands of central-west Argentina, rodent diversity is dominated by Phyllotis vaccarum, Abrothrix andina, Akodon oenos, and Euneomys sp. that coexist in different sections of their elevational ranges. Although these species' diets are relatively flexible, it is unclear how temperature and food availability influence their constitution. To unveil this, we explored their feeding strategies at different elevations (1700, 2300, and 3100 m a.s.l.) and seasons (winter and spring-summer). By examining fecal samples, we quantified the intake of vegetative parts of plants, seeds, and arthropods. Abrothrix andina was insectivorous at 2300 m and omnivorous at 3100 m a.s.l. in line with the OHM predictions, suggesting a higher plant consumption derived from an increased capacity of digestive organs, favored by lower temperatures at higher elevations. Phyllotis vaccarum was herbivorous at all elevations, independently of food supply or temperature conditions. However, the secondary food choice occurred in line with the OHM predictions, suggesting a certain degree of digestive adjustment to ambient temperature. Akodon oenos, which was only captured at 2300 m, was insectivorous, whereas Euneomys sp., which was only present at 3100 m, was a specialist herbivore. We detected no seasonal variation in the feeding strategies of the rodents examined. Intraspecifically, thermoregulatory demands would influence the variation in feeding strategies at the elevational gradient, whereas nutritional requirements would explain their consistency between seasons. Interspecifically, we found that diet dissimilarity was relatively high, mainly at high elevations and during winter, which could facilitate species coexistence.